Porosimetry for Thin Films of Metal–Organic Frameworks: A Comparison of Positron Annihilation Lifetime Spectroscopy and Adsorption‐Based Methods. Issue 17 (17th March 2021) - Stassin, Timothée; Verbeke, Rhea; Cruz, Alexander John; Rodríguez‐Hermida, Sabina; Stassen, Ivo; Marreiros, João; Krishtab, Mikhail; Dickmann, Marcel; Egger, Werner; Vankelecom, Ivo F. J.; Furukawa, Shuhei; De Vos, Dirk; et al.
Abstract: Thin films of crystalline and porous metal–organic frameworks (MOFs) have great potential in membranes, sensors, and microelectronic chips. While the morphology and crystallinity of MOF films can be evaluated using widely available techniques, characterizing their pore size, pore volume, and specific surface area is challenging due to the low amount of material and substrate effects. Positron annihilation lifetime spectroscopy (PALS) is introduced as a powerful method to obtain pore size information and depth profiling in MOF films. The complementarity of this approach to established physisorption‐based methods such as quartz crystal microbalance (QCM) gravimetry, ellipsometric porosimetry (EP), and Kr physisorption (KrP) is illustrated. This comprehensive discussion on MOF thin film porosimetry is supported by experimental data for thin films of ZIF‐8. Abstract : The porosity characterization of metal–organic frameworks deposited as thin films on surfaces is challenging and requires a combination of techniques. The use of positron annihilation lifetime spectroscopy is introduced, and it is compared in a comprehensive and tutorial way to conventional adsorption‐based methods (quartz crystal microbalance gravimetry, ellipsometric porosimetry, and krypton physisorption).